Biological Emulation of Selective Attention of Visual Light Communication Sensor in Environments with Light Noise - Canete-Arratia, L; Canete-Arratia, L (Institute of Electrical and Electronics Engineers Inc., 2018)
In order to improve the performance of autonomous sensory systems that work by means of Visual Light Communication (VLC) where their receiver is searching for the target transmitters in a complex environment containing several light sources, it emulates the behavior of animals when they search for food in fuzzy fields. In this context, eco-cognitive studies in predators have established this relationship between the detection of a particular food and the attention: Pi α (Ai) 1/Kl, where Pi is the probability of detecting the prey i, Ai is the fraction of the predator s attention devoted to prey and Ki is the index of prey s distinction in the environment. This biological phenomenon is emulated in the function of a single intelligent receiver when it is seeking data from a transmitter placed in noise environment, quantifying any of these three variables given the other two. This kind of ecological model allows managers to get better the achievements of VLC in environments with light noise where the scarcity of both energy and information, is always omnipresent; surpassing in about a quarter the performance of a system lacking this emulation. © 2017 IEEE.